Can Innovation Enhance Regional Governments Performance in Indonesia? - Lindawati Lindawati; Sak Khie (Universitas Negeri Malang, 2024)
In Indonesia, innovation has become an essential priority for the government. The study analysed innovation's impact on regional governments' performance. The study focused on factors such as regional financial independence, local own-sourced revenue growth rate, the maturity level of e-government, and regional competitiveness. Secondary data from related ministries, covering all provincial, regency, and city governments in Indonesia, were used for the analysis. The study tested hypotheses using partial least squares and group difference tests. The results indicated that innovation positively impacted regional financial independence, e-government maturity level, and regional competitiveness but did not impact local own-sourced revenue growth rate. Innovative local governments exhibited higher regional financial independence, e-government maturity level, and competitiveness index. As a result, the study concluded that innovation plays a significant role in improving local government performance by helping manage resource constraints and meeting societal expectations. However, the regional financial independence dominated by low levels highlights the need for better innovation and performance management, especially in increasing revenue to better finance regional development.